What are the characteristics of the cases we use to teach and learn evaluation?. Issue 172 (24th February 2022) - Kallemeyn, Leanne M.; Titiml, Eleanor N.; Galib, Linda; Castelin, Kim; Montrosse‐Moorhead, Bianca; Ensminger, David C.; Linfield, Kenneth J.
Abstract: Case‐centered teaching and learning is important for illustrating evaluation approaches, practicing professional problem‐solving and ethical decision‐making, and teaching professional skills and competencies. In this study we provide findings on a content analysis of 148 written cases used to teach evaluation and a critical analysis of five purposively selected cases. The findings demonstrate that evaluators have written many cases to teach the situational nature of evaluation practice. Most of the cases are simulations of practice, which include how the case actors' think, decide, and act in an evaluation context. The study findings point to several areas for strengthening case‐centered teaching in evaluation, including providing clear learning objectives, developing supporting resources for instructors, aligning cases with professional competencies and/or core concepts in the field, developing cases to promote active and problem‐based learning, ensuring cases represent equity‐informed practices, and broadening the representation of diverse people and contexts.